Предмет: Алгебра,
автор: animetelli
Решить уравнение:
1-x-x²=x-(x-2)(x+3)
Ответы
Автор ответа:
0
1-х-х в квадрате = х-( х в квадрате +3х -2х -6)
1-х-х в квадрате = х-х в квадрате -3х +2х+6
1-х-х+3х-2х-6=0
-х=5
х=-5
1-х-х в квадрате = х-х в квадрате -3х +2х+6
1-х-х+3х-2х-6=0
-х=5
х=-5
Похожие вопросы
Предмет: Другие предметы,
автор: Diana270700
Предмет: Физика,
автор: Аноним
Предмет: Қазақ тiлi,
автор: gulmirashinarbaeva
Предмет: Физика,
автор: kutmankazybeko
Предмет: Физика,
автор: rafailmurshito